1975
DOI: 10.1073/pnas.72.6.2125
|View full text |Cite
|
Sign up to set email alerts
|

Human X-Linked genes regionally mapped utilizing X-autosome translocations and somatic cell hybrids.

Abstract: Human genes coding for hypoxanthine phosphoribosyltransferase (HPRT, EC 2.4.2.8; IMP:pyrophosphate phosphoribosyltransferase), glucose-6-phosphate dehydrogenase (G6PD, EC 1.1.1.49; D-glucose-6-phosphate: NADP+ 1-oxidoreductase), and phosphoglycerate kinase (PGK, EC 2.7.2.3; ATP:3-phospho-D-glycerate 1-phosphotransferase) have been assigned to specific regions on the long arm of the X chromosome by somatic cell genetic techniques. Gene assignment and linear order were determined by employing human somatic cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1976
1976
1992
1992

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…2B). Two distinct GK-3- Table 1 were identified by karyotypic analysis and chromosome-specific enzyme markers (59,62). The percent discordant segregation indicates that no chromosome other than human chromosome 17 cosegregated with all of the samples showing GK-3 hybridization.…”
Section: Group Of Keratin Genes Onmentioning
confidence: 99%
“…2B). Two distinct GK-3- Table 1 were identified by karyotypic analysis and chromosome-specific enzyme markers (59,62). The percent discordant segregation indicates that no chromosome other than human chromosome 17 cosegregated with all of the samples showing GK-3 hybridization.…”
Section: Group Of Keratin Genes Onmentioning
confidence: 99%
“…5 Giemsatrypsin and Giemsa-9 banding were used to identify the chromosomes as described. 3 and chromosome 9 did not segregate concordantly (table II). These data do not support the assignment of ¡¡GUS to chromosome 9.…”
mentioning
confidence: 99%
“…Gel electrophoresis for identifying the enzyme phenotype was performed as described.1'5 Giemsa-trypsin and Giemsa-9 banding were used to identify the chromosomes as described. 3 groups was observed, eliminating all but chromosomes 3, 4, 7, and 8 as the chromosomes on which fiGUS is located. Chromosome and enzyme studies on 14 man-mouse cell hybrids demonstrated that fiGUS and chromosome 7 segregated concordantly (table I).…”
mentioning
confidence: 99%
“…The origin and isolation of the hybrids used in this investigation have been described elsewhere (Croce and Koprowski, 1974;Shows and Brown, 1975;Ciiern and Croce. 1976;Croce.…”
Section: Methodsmentioning
confidence: 99%